Factors attributing to initiation of tobacco use in adolescent students of Moradabad, (UP) India - Ravishankar, TL; Nagarajappa, Ramesh (Indian journal of dental research, 2009)
Tobacco consumption is a major health menace owing to its widespread use particularly among adolescents. Owing to the presence of impressionable, curious minds, adolescents are highly prone to a number of influences within and outside home, leading them to experiment with tobacco. The addictive nature of tobacco is potent enough to turn these experimental users to addicts. To identify the prominent factors leading to initiation of tobacco use among adolescents of Moradabad. Two-stage sampling was used to identify 590 adolescents (study population) from four senior secondary schools in Moradabad. The response towards tobacco, and its use, was assessed through structured questionnaires. Responses of all study population and association between dependent and explanatory variables were assessed using chi2 test (Chi-square test) using SPSS package (version 12). The study results show that 17.3% of the adolescents have experimented with tobacco. Curiosity and peer pressure were the main reasons behind trying tobacco. Parental tobacco status, especially place of use (at home or outside), had a significant influence on adolescents experimenting tobacco. Tobacco use by parents is likely to influence adolescents, as they perceive tobacco use as a positive and acceptable behavior, and develop favorable personal beliefs and subjective norms towards tobacco use.